Molecular biology - Clark, David P.
"Molecular Biology, Third Edition, provides a thoroughly revised, invaluable resource for college and university students in the life sciences, medicine and related fields. This esteemed text continues to meet the needs of students and professors by offering new chapters on RNA, genome defense, and epigenetics, along with expanded coverage of RNAi, CRISPR, and more ensuring topical content for a new class of students. This volume effectively introduces basic concepts that are followed by more specific applications as the text evolves"--Publisher's description.